Assessment of Cost and Returns of Cattle Marketing In Central Zone of Adamawa State, Nigeria. - Girei, A.; Dire and B. H. Bello, B. (British Journal of Marketing Studies, 2013)
The study was to assess the cost and returns in cattle marketing in central Adamawa State, Nigeria. Data for this study were collected from activities of cattle marketer for the year 2012. The data were collected using structured questionnaire. One hundred and twenty (120) Cattle marketers were administered with questionnaires. A total of Ninety questionnaires were used for analyzed. However, both descriptive (frequency, percentage and mean) and inferential statistics was used for analyzing the data generated from the study. Analysis of the structure and performance of cattle marketers was done using Gini coefficient and marketing margin analysis. The results obtained from the study revealed that, performance of cattle marketers which was analyzed using marketing margin techniques was found to be 9.09 percent. This indicates that, marketers obtained 9.09 percent of the final sales which is paid by the consumers. Also, the analysis of seller concentration of cattle marketing shows that, a Gini coefficient of 0.65 was obtained. The relatively high Gini coefficient which by the analysis tends to approach one (1) is a clear indication of inequality in earnings from the sales of the animals and high marketing concentration. The study therefore recommends that, marketers should form / strengthening their associations and cooperatives for extensive information sharing and in-leading between and among members, government at all levels should also be willing to provide information to marketers and researchers so as to help in addressing the problems associated with cattle marketing for necessary support and legislations